KONSEP PENDIDIKAN KARAKTER ANAK MENURUT IMAM AL-GHAZALI DALAM KITAB AYYUHA AL-WALAD - Muhammad Hafijhin (STAI AL FALAH Banjarbaru, 2018)
The main problem of this research is to assess the concept of child character education according to Imam Al-Ghazali from the advice contained in the book of Ayyuha Al-Walad. While the formulation of the problem in this study is how the concept of child character education according to Imam Al-Ghazali and the factors that influence the formation of the character of children according to Al-Ghazali in the book Ayyuha Al-Walad. The data presented in this study surrendered from the book of Ayyuha Al-Walad. In addition, it is also supported by several works by Imam Al-Ghazali regarding the character education of children. Thus this research is commonly classified in the type of library research (library research). Faith Al-Ghazali argues that human character can be shaped in such a way. Of course with continuous training and strong desire. In addition, he also provides several methods to be applied in the education process in order to be a good and noble figure, all of which is certainly related to the example of the educator, both parents at home, and teachers at school and the influence of the surrounding environment. After observing and comparing among the concepts of child character education according to Imam Al-Ghazali and the concept of character education in general which is applied today, the authors find that there are many similarities in character education values of the two concepts, which all lead to the formation of noble character as taught by the Messenger of Allah. To his people. Keywords: Character, Education, Al-Ghazali, Ayyuha Al-Walad.